Study on Foreign Homeownership in Johor Bahru, Johor - Eiap, Vien Kien; Omar, Abdul Jalil (Research in Management of Technology and Business, 2025)
This study explores the phenomenon of home ownership by foreign citizens in Johor Bahru, a significant issue with broad economic and social implications. Using a quantitative approach through surveys and structured interviews with foreign buyers and real estate agents, the study examines the key factors driving foreign property purchases and their preferred property types. The findings reveal that strategic location, competitive property prices, and government initiatives such as the minimum property value requirement and the Malaysia My Second Home (MM2H) program are major attractions. Luxury condominiums and double-storey terrace houses emerge as the top property choices among foreign buyers. Additionally, the purchasing process for foreigners shows minimal differences in terms of personal documentation compared to Malaysian citizens. The study offers valuable insights for policymakers and property developers to balance foreign investment interests with the needs of local residents. It also recommends inclusive and sustainable property development strategies to promote balanced economic growth and equitable housing opportunities for all.